2005
DOI: 10.1074/jbc.m509378200
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel-like Factor 4 Is a Mediator of Proinflammatory Signaling in Macrophages

Abstract: Activation of macrophages is important in chronic inflammatory disease states such as atherosclerosis. Proinflammatory cytokines such as interferon-␥ (IFN-␥), lipopolysaccharide (LPS), or tumor necrosis factor-␣ can promote macrophage activation. Conversely, anti-inflammatory factors such as transforming growth factor-␤1 (TGF-␤1) can decrease proinflammatory activation. The molecular mediators regulating the balance of these opposing effectors remain incompletely understood. Herein, we identify Kruppel-like fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
296
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(312 citation statements)
references
References 78 publications
14
296
0
2
Order By: Relevance
“…As SMCs are responsible for production of elastic fibers 38 and extracellular matrix, their death may cause a decline in contractile element synthesis and vessel wall structural integrity that ultimately lead to aneurysm formation or progression. 39 The underlying mechanism may occur through TNF-a upregulation of KLF4, as KLF4 has been shown to activate macrophages, 40 which not only induce expression MMPs in aneurysms, but also have a key role in apoptosis and phagocytosis of SMCs leading to aneurysm progression. 28,30 The number of such apoptotic cells has been shown to correlate with the probability of rupture of cerebral aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…As SMCs are responsible for production of elastic fibers 38 and extracellular matrix, their death may cause a decline in contractile element synthesis and vessel wall structural integrity that ultimately lead to aneurysm formation or progression. 39 The underlying mechanism may occur through TNF-a upregulation of KLF4, as KLF4 has been shown to activate macrophages, 40 which not only induce expression MMPs in aneurysms, but also have a key role in apoptosis and phagocytosis of SMCs leading to aneurysm progression. 28,30 The number of such apoptotic cells has been shown to correlate with the probability of rupture of cerebral aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work has implicated KLF4 as being important in a broad range of cellular processes such as endothelial pro-inflammatory activation [83], macrophage gene expression [35], tumor cell development [30] and stem cell biology [36,84].…”
Section: Klf4mentioning
confidence: 99%
“…Because Icsbp belongs to the classic ISGs stimulated by either IFN-α or IFN-γ (24, 25), we then examined whether the expressions of other ISGs might also be affected by Rig-I deficiency. By comparing the mRNA expression profile of Rig-I −/− granulocytes with that of Rig-I +/+ granulocytes, we found that two additional classic ISGs, Klf4 and Trail (26,27), also appeared in the top-ranked genes whose expression was greatly reduced by Rig-I deficiency in BM granulocyte progenitors or mature granulocytes ( Fig. 2A).…”
Section: Rig-i Induction Functionally Contributes To Ifn Plus Atra-inmentioning
confidence: 99%